2008 14th IEEE International Conference on Parallel and Distributed Systems 2008
DOI: 10.1109/icpads.2008.47
|View full text |Cite
|
Sign up to set email alerts
|

Pipelined Parallel AC-Based Approach for Multi-String Matching

Abstract: New applications such as real-time packet processing require high-speed string matcher, and the number of strings in pattern store is increasing to tens of thousands, which requires a memory efficient solution. In this paper, a pipelined parallel approach for hardware implementation of Aho-Corasick (AC) algorithm for multiple strings matching called P2-AC is presented. P2-AC organizes the transition rules in multiple stages and processes in pipeline manner, which significantly simplifies the DFA state transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Wei Lin and Bin Liu have presented a study on an improved Aho-Corasick algorithm, which is called P2-AC on SRAM [8]. The authors suggested a pipelined parallel approach on SRAMs.…”
Section: Related Workmentioning
confidence: 99%
“…Wei Lin and Bin Liu have presented a study on an improved Aho-Corasick algorithm, which is called P2-AC on SRAM [8]. The authors suggested a pipelined parallel approach on SRAMs.…”
Section: Related Workmentioning
confidence: 99%
“…Other hardware-based architectures also have been proposed using memory and combinatorial logic elements. In [9], the authors proposed a pipelined approach with parallel SRAMs for hardware implementation of the Aho-Corasick algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the space required for the transitions can be reduced. Pao et al [35] and W. Lin and B. Liu [36] proposed pipeline architectures to implement the partial trie that only contains goto functions of the AC-trie so that it can reduce the space induced by failure functions. N. Hua et al [37] proposed another approach based on a block-oriented scheme instead of usually byte-oriented processing of patterns to reduce the memory usage.…”
Section: Fig 3 Number Of Patterns Vs Relative Instructionsmentioning
confidence: 99%
“…Wei Lin, Bin Liu [30] presented a pipelined parallel approach for hardware implementation of Aho-Corasick (AC) algorithm for multiple strings matching called P2-AC. P2-AC organizes the transition rules in multiple stages and processes in pipeline manner, which significantly simplifies the DFA state transition graph into a character tree that only contains forwarding edges.…”
Section: Aho Corasick Based Approachesmentioning
confidence: 99%